5.20.17 Problems 1601 to 1700

Table 5.939: Second or higher order ODE with constant coefficients

#

ODE

Mathematica

Maple

7948

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

7949

\[ {}y^{\prime \prime } = 4 y \]

7950

\[ {}4 y^{\prime \prime }-8 y^{\prime }+7 y = 0 \]

7951

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

7952

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7953

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7954

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = 0 \]

7955

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

7956

\[ {}y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

7957

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

7958

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7959

\[ {}y^{\prime \prime }+4 y^{\prime }+2 y = 0 \]

7960

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

7970

\[ {}y^{\prime \prime }+3 y^{\prime }-10 y = 6 \,{\mathrm e}^{4 x} \]

7971

\[ {}y^{\prime \prime }+4 y = 3 \sin \left (x \right ) \]

7972

\[ {}y^{\prime \prime }+10 y^{\prime }+25 y = 14 \,{\mathrm e}^{-5 x} \]

7973

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 25 x^{2}+12 \]

7974

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 20 \,{\mathrm e}^{-2 x} \]

7975

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 14 \sin \left (2 x \right )-18 \cos \left (2 x \right ) \]

7976

\[ {}y^{\prime \prime }+y = 2 \cos \left (x \right ) \]

7977

\[ {}y^{\prime \prime }-2 y^{\prime } = 12 x -10 \]

7978

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 6 \,{\mathrm e}^{x} \]

7979

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = {\mathrm e}^{x} \sin \left (x \right ) \]

7980

\[ {}y^{\prime \prime }+y^{\prime } = 10 x^{4}+2 \]

7981

\[ {}y^{\prime \prime }+4 y = 4 \cos \left (2 x \right )+6 \cos \left (x \right )+8 x^{2}-4 x \]

7982

\[ {}y^{\prime \prime }+9 y = 2 \sin \left (3 x \right )+4 \sin \left (x \right )-26 \,{\mathrm e}^{-2 x}+27 x^{3} \]

7983

\[ {}y^{\prime \prime }-3 y = {\mathrm e}^{2 x} \]

7984

\[ {}y^{\prime \prime \prime }+y^{\prime } = \sin \left (x \right ) \]

7985

\[ {}y^{\prime \prime }+4 y = \tan \left (2 x \right ) \]

7986

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-x} \ln \left (x \right ) \]

7987

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 64 x \,{\mathrm e}^{-x} \]

7988

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{-x} \sec \left (2 x \right ) \]

7989

\[ {}2 y^{\prime \prime }+3 y^{\prime }+y = {\mathrm e}^{-3 x} \]

7990

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \frac {1}{1+{\mathrm e}^{-x}} \]

7991

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

7992

\[ {}y^{\prime \prime }+y = \cot \left (x \right )^{2} \]

7993

\[ {}y^{\prime \prime }+y = \cot \left (2 x \right ) \]

7994

\[ {}y^{\prime \prime }+y = x \cos \left (x \right ) \]

7995

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

7996

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \tan \left (x \right ) \]

7997

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \csc \left (x \right ) \]

7998

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 x \]

7999

\[ {}y^{\prime \prime }-y^{\prime }-6 y = {\mathrm e}^{-x} \]

8005

\[ {}y^{\prime \prime }+y = 0 \]

8006

\[ {}y^{\prime \prime }-y = 0 \]

8016

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 0 \]

8017

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-2 y = 0 \]

8018

\[ {}y^{\prime \prime \prime }-y = 0 \]

8019

\[ {}y^{\prime \prime \prime }+y = 0 \]

8020

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = 0 \]

8021

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+6 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

8022

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

8023

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = 0 \]

8024

\[ {}y^{\prime \prime \prime \prime }-2 a^{2} y^{\prime \prime }+a^{4} y = 0 \]

8025

\[ {}y^{\prime \prime \prime \prime }+2 a^{2} y^{\prime \prime }+a^{4} y = 0 \]

8026

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

8027

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

8028

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0 \]

8029

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }-3 y^{\prime \prime }-5 y^{\prime }-2 y = 0 \]

8030

\[ {}y^{\left (5\right )}-6 y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+48 y^{\prime \prime }+16 y^{\prime }-96 y = 0 \]

8031

\[ {}y^{\prime \prime \prime \prime } = 0 \]

8032

\[ {}y^{\prime \prime \prime \prime } = \sin \left (x \right )+24 \]

8033

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 10+42 \,{\mathrm e}^{3 x} \]

8034

\[ {}y^{\prime \prime \prime }-y^{\prime } = 1 \]

8039

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

8040

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

8041

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

8042

\[ {}y^{\prime \prime }-y^{\prime }+6 y = 0 \]

8043

\[ {}y^{\prime \prime }-2 y^{\prime }-5 y = x \]

8044

\[ {}y^{\prime \prime }+y = {\mathrm e}^{x} \]

8045

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

8046

\[ {}y^{\prime \prime }-y = {\mathrm e}^{3 x} \]

8047

\[ {}y^{\prime \prime }+9 y = 0 \]

8048

\[ {}y^{\prime \prime }-y^{\prime }+4 y = x \]

8049

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{x} \]

8050

\[ {}y^{\prime \prime }+3 y^{\prime }+4 y = \sin \left (x \right ) \]

8051

\[ {}y^{\prime \prime }+y = {\mathrm e}^{-x} \]

8052

\[ {}y^{\prime \prime }-y = \cos \left (x \right ) \]

8053

\[ {}y^{\prime \prime } = \tan \left (x \right ) \]

8054

\[ {}y^{\prime \prime }-2 y^{\prime } = \ln \left (x \right ) \]

8055

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 2 x -1 \]

8056

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{-x} \]

8057

\[ {}y^{\prime \prime }-y^{\prime }-2 y = \cos \left (x \right ) \]

8058

\[ {}y^{\prime \prime }+2 y^{\prime }-y = x \,{\mathrm e}^{x} \sin \left (x \right ) \]

8059

\[ {}y^{\prime \prime }+9 y = \sec \left (2 x \right ) \]

8060

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = x \ln \left (x \right ) \]

8062

\[ {}y^{\prime \prime }+4 y = \tan \left (x \right )^{2} \]

8063

\[ {}y^{\prime \prime }-y = 3 \,{\mathrm e}^{2 x} \]

8064

\[ {}y^{\prime \prime }+y = -8 \sin \left (3 x \right ) \]

8065

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{2}+2 x +2 \]

8066

\[ {}y^{\prime \prime }+y^{\prime } = \frac {x -1}{x} \]

8068

\[ {}y^{\prime \prime }+9 y = -3 \cos \left (2 x \right ) \]

8070

\[ {}y^{\prime \prime } = -3 y \]

8167

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 5 \,{\mathrm e}^{3 t} \]

8168

\[ {}y^{\prime \prime }+y^{\prime }-6 y = t \]

8169

\[ {}y^{\prime \prime }-y = t^{2} \]

8173

\[ {}y^{\prime \prime }+3 y^{\prime }-5 y = 1 \]

8174

\[ {}y^{\prime \prime }+3 y^{\prime }-2 y = -6 \,{\mathrm e}^{-t +\pi } \]

8175

\[ {}y^{\prime \prime }+2 y^{\prime }-y = t \,{\mathrm e}^{-t} \]

8176

\[ {}y^{\prime \prime }-y^{\prime }+y = 3 \,{\mathrm e}^{-t} \]